The importance of the dentist in the diagnosis of Cowden syndrome: case report - Viegas, Camila Feier; Pires, Tulio de Lucena; Figueiredo, Paulo Tadeu de Souza; Leite, Andre Ferreira; Mesquita, Clemes Alves (Brazilian Dental Science, 2016)
Cowden Syndrome is an autosomal dominant disorder characterized by the development of several hamartomas in a variety of tissues, including the skin, gastrointestinal tract, adipose tissue, and bone and connective tissues. This syndrome is associated with a high risk of developing malignancies, especially breast, thyroid and endometrium cancers. This report presents a case of a 53-year-old patient who sought assistance at the Dentistry Department of the University Hospital of Brasilia (HUB) to receive basic dental treatment. The current and past medical history and oral and facial manifestations led to the diagnosis of Cowden syndrome. This case report aims to highlight the importance of a dental surgeon in the diagnosis of this syndrome, based on the observation of oral manifestations and medical history.KeywordsCowden Syndrome; Multiple Hamartoma Syndrome.